Green Extraction Of Anthocyanins From Roselle: A Comparative Evaluation Of Extraction Techniques And Solvents - Raihanah Roslan; Muhammad Azri Mohamad Fauzi; Natashah Emira Ahmad Amran; Syamila Mansor; Kiki Adi Kurnia; Muhammad Syafiq Hazwan Ruslan (Faculty of Engineering, KhonKaen University, Thailand, 2025)
Indexed